Culture creating existence: functions and general principles of development - Fed, Volodymyr (Skhid, 2013)
In the article the problem of determination of culture creating existence functions is considered. The nature and interaction of these functions are investigated as well. This article also contains author’s understanding of the general principles of culture creating development